1976
DOI: 10.1017/s0043174500065802
|View full text |Cite
|
Sign up to set email alerts
|

Competition of Velvetleaf, Prickly Sida, and Venice Mallow in Soybeans

Abstract: Weed competition in soybeans [Glycine max(L.) Merr. ‘Clark 63′] with planted stands of velvetleaf (Abutilon theophrastiMedic.), prickly sida (Sida spinosaL.), and Venice mallow (Hibiscus trionumL.) is reported. Weeds were planted 0, 10, 20, 30, and 40 days after soybeans and competed until soybeans matured. Soybean seed yields were reduced 720, 250, and 230 kg/ha by velvetleaf, Venice mallow, and prickly sida, respectively. Weeds that emerged with soybeans reduced yields 1,010 kg/ha. Weeds planted 10 days late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
91
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 14 publications
11
91
0
Order By: Relevance
“…Prickly sida competes with several crops, including cotton {Gossypium hirsutum L.) (Buchanan, Crowley & McLaughlin, 1977) and soybean {Glycine max (L.) Merr.) (Eaton, Russ & Feltner, 1976). Prickly sida exhibited more than 85% germination in light or darkness at 35°C (Egley, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Prickly sida competes with several crops, including cotton {Gossypium hirsutum L.) (Buchanan, Crowley & McLaughlin, 1977) and soybean {Glycine max (L.) Merr.) (Eaton, Russ & Feltner, 1976). Prickly sida exhibited more than 85% germination in light or darkness at 35°C (Egley, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…cantly, while the number of stems in each transect segment remained about the same (Table 1). Eaton et al (1976) also reported that velvetleaf interference reduced the number of pods/stem more than any other soybean-yield component. These data indicate that velvetleaf presence interferes with soybeans, although it does not separate the effects of competition from allelopathy.…”
Section: Materials Andmentioning
confidence: 95%
“…is an annual weed of wide distribution in eastern United States and the more mesic regions of the prairie states. Eaton et al (1976) reported soybean seed yield losses as high as 720 kg/ha due to the presence of velvetleaf. Velvetleaf-related yield reductions in cotton (Gossypium hirsutum L.) and soybean have been attributed to the strong competitive nature of this plant and no attention has been directed to biochemical interference (Staniforth and Weber, 1956;Staniforth, 1965;Eaton, Russ, and Feltner, 1976;Chandler, 1977).…”
mentioning
confidence: 99%
“…One to two plants m~^ of weeds such as velvetleaf (A. f/teop/ira^ft), jimsonweed {Datura stramonium L.), and cocklebur {Xanthium strumarium L.) shaded all of the surrounding soybean plants when allowed to grow taller than the crop (Stoller & Wooley, 1985). Shading by weeds taller than soybeans accounted for 86% of the predicted 19-25% decrease in soybean productivity-Different levels of soybean loss attributable to A. theophrasti interference have been reported depending upon weed density (Dekker & Meggitt, 1983;Hagood et al, 1980;Oliver, 1979), duration of competition (Eaton e/ al., 1976), planting date (Oliver, 1979) and date of A. theophrasti emergence (Hagood et ai, 1980;Eaton « a/-, 1976).…”
Section: Introductionmentioning
confidence: 93%
“…Weeds present during the first two to four weeks after soybean emergence sometimes diminish yields (Eaton, Feltner & Russ, 1973;Eaton, Russ & Feltner, 1976). The reason for this reduction has not been determined.…”
Section: Introductionmentioning
confidence: 99%